Lung Metastases: Current Surgical Indications and New Perspectives - Mangiameli, Giuseppe; Cioffi, Ugo; Alloisio, Marco; Testori, Alberto (Frontiers in Surgery, 2022)
Pulmonary metastasectomy is an established treatment that can provide improved long- term survival for patients with metastatic tumor(s) in the lung. In this mini-review, we discuss the state of art of thoracic surgery in surgical management of lung metastases which actually occurs for a large part of surgical activity in thoracic surgery department. We describe the principles of surgical therapy that have been defined across the time, and that should remain the milestones of lung metastases treatment: a radical surgery and an adequate lymphadenectomy. We then focus on current surgical indications and report the oncological results according to the surgical approach (open vs mini-invasive), the histological type and number of lung metastases, and in case of re-metastasectomy. Finally, we conclude with a brief overview about the future perspectives in thoracic surgery in treatment of lung metastases.